Analysis of 21st Century Skills in the Implementation of Project Based Learning in Biology Learning Merdeka Curriculum - Mia Roosmalisa Dewi; Zainal Arifin (Jurnal Penelitian Pendidikan IPA, 2024)
21st century skills are important skills that every student must have to be prepared to face global challenges. One of the innovative learning models that can improve 21st century skills is project-based learning. Project Based Learning is one of the main characteristics in the implementation of the Merdeka Curriculum. This study aims to analyze the 21st century skills of students in the implementation of project based learning in merdeka curriculum especially in the biology subject. This research uses a quantitative descriptive method with case study strategy. Data were obtained from the observation process. The observation instrument used represents four categories of 21st century skills namely critical thinking, creativity and inovation, communication, and collaboration. Based on the results, it can be known that communication skills have the most approaching standard and standard categories among other skills. Furthermore, for creativity and innovation, in this study the results show that there are still many students in the category below standard and approaching standard. Therefore, it can be concluded from the results of the study that most of student  are still at an intermediate level for 21st century skills but the results might different depending on the grade level,  characteristics students, subject area and teacher